Innovative Assessment Methods: Enhancing Student Learning through Formative Assessment and Peer Review - Hasanatun Latifah; Mohamad Ardin Suwandi (PT Mutiara Bustan Ilmu, 2024)
This study investigates the effectiveness of formative assessments and peer reviews in enhancing student learning outcomes in educational settings. Through a mixed-methods approach, quantitative data were collected via pre- and post-test scores, while qualitative insights were gathered from student and teacher interviews. The results reveal a significant improvement in student performance following the implementation of formative assessments, particularly among low-performing students. Additionally, qualitative findings indicate that students generally view formative assessments as beneficial for self-regulation and learning control, despite some challenges related to workload and stress. Teacher feedback highlighted the importance of these assessment methods in adapting instruction and monitoring progress, although concerns about time and resource allocation were also noted. The study underscores the need for careful implementation of formative assessments and peer reviews to maximize their effectiveness while addressing the associated challenges.